Development and acceptability of diagnostic drill cards in algebra - Estrera, Ernie P.; Leyva, Myra M.; Padua, Alice E. (2014)
Executive Summary: This study aimed to develop a Diagnostic Drill Cards which may supplement learning and determine the level of acceptability of the developed Diagnostic Drill Cards in Algebra as evaluated by the Mathematics teachers in University of Rizal System - Morong. This study was conducted by the researchers to come up with a material that can be used as a supplement to help students to learn the fundamental operation on monomials and integers. The researcher decided to pursue this study for the betterment of the quality education that the teacher may render to their students. Descriptive development methods was employed in the study which utilized adopted-modified questionnaire-checklist in terms of content, appearance, usefulness and durability for these methodologies were appropriate to be used. The developed Diagnostic Drill Cards are very much acceptable material in Algebra as evaluated by the mathematics teachers with respect to content, appearance, usefulness and durability. The researchers recommend the utilization of Diagnostic Drill Cards by the teachers to facilitate teaching-learning process and develop the skills in understanding basic concepts in Algebra and the researchers recommend the conduct follow up study on the effectiveness of the developed Diagnostic Drill Cards as an instructional material in teaching Algebra.
Keywords: Teaching -- Aids and devices